Clinical features, cytology and bacterial culture results in dogs with and without cheilitis and comparison of three sampling techniques. Issue 3 (28th March 2016) - Doelle, Maren; Loeffler, Anette; Wolf, Katharina; Kostka, Veit; Linek, Monika
Abstract : Background: Cheilitis is a common presentation in dogs associated with a variety of skin diseases and often complicated by microbial infections. Objectives: To describe and compare clinical and cytological features and bacterial culture results from the lower lips of dogs with cheilitis (as compared to healthy controls), and to evaluate three cytology sampling techniques for their abilities to differentiate between the groups. Animals: Fifty six dogs with cheilitis and 54 controls. Methods: Anatomy and clinical signs of the lower lip were recorded. Cytology samples taken by tape strip, direct impression and swabs rolled over skin were scored semiquantitatively for microorganisms, inflammatory cells and keratinocytes. Cytology scores were correlated with semiquantitative bacterial culture scores. Results: Pure breeds, frequency of lip folds and all cytology scores except keratinocytes were higher in dogs with cheilitis than in controls, but a substantial overlap was seen in all microorganisms between the groups. Hypersensitivity disorders were diagnosed in 40 of 56 dogs with cheilitis. The tape strip technique yielded the greatest differences between groups. Bacterial growth was reported in 100% of dogs with cheilitis and in 93% of the controls. Pathogens such as Staphylococcus pseudintermedius, Escherichia coli and Pseudomonas spp were found more frequently in dogs with cheilitis. Cytology and bacterial culture were poorly correlated. Conclusion: Cheilitis was associated with primary hypersensitivity disorders and the presence of a lip fold was a predisposing factor. Results of aerobic culture were similar to prior studies on pyoderma of other body sites, except for higher rates of Pseudomonas spp. isolation. Abstract : Background – Cheilitis is a common presentation in dogs associated with a variety of skin diseases and often complicated by microbial infections.Objectives – To describe and compare clinical and cytological features and bacterial culture results from the lower lips of dogs with cheilitis (as compared to healthy controls), and to evaluate three cytology sampling techniques for their abilities to differentiate between the groups.Conclusion – Cheilitis was associated with primary hypersensitivity disorders and the presence of a lip fold was a predisposing factor. Results of aerobic culture were similar to prior studies on pyoderma of other body sites, except for higher rates of Pseudomonas spp. isolation.